Birth characteristics of children who used early intervention and special education services in New York City. (28th December 2019) - Romo, Matthew L; McVeigh, Katharine H; Jordan, Phoebe; Stingone, Jeanette A; Chan, Pui Ying; Askew, George L
Abstract: Background: Early intervention (EI) and special education (SE) are beneficial for children with developmental disabilities and/or delays and their families, yet there are disparities in service use. We sought to identify the birth characteristics that predict EI/SE service use patterns. Methods: We conducted a retrospective cohort study using linked administrative data from five sources for all children born in 1998 to New York City resident mothers. Multinomial regression was used to identify birth characteristics that predicted predominant patterns of service use. Results: Children with service use patterns characterized by late or limited/no EI use were more likely to be first-born children and have Black or Latina mothers. Children born with a gestational age ≤31 weeks were more likely to enter services early. Early term gestational age was associated with patterns of service use common to children with pervasive developmental delay, and maternal obesity was associated with the initiation of speech therapy at the time of entry into school. Conclusions: Maternal racial disparities existed for patterns of EI/SE service use. Specific birth characteristics, such as parity and gestational age, may be useful to better identify children who are at risk for suboptimal EI use.